2023
DOI: 10.3390/cells12050822
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Soybean Paste Attenuates Biogenic Amine-Induced Liver Damage in Obese Mice

Abstract: Biogenic amines are cellular components produced by the decarboxylation of amino acids; however, excessive biogenic amine production causes adverse health problems. The relationship between hepatic damage and biogenic amine levels in nonalcoholic fatty liver disease (NAFLD) remains unclear. In this study, mice were fed a high-fat diet (HFD) for 10 weeks to induce obesity, presenting early-stage of NAFLD. We administered histamine (20 mg/kg) + tyramine (100 mg/kg) via oral gavage for 6 days to mice with HFD-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“… 35 Increased levels of its metabolite histamine lead to elevated levels of PARP-1 and IL-1β, as well as MAO-A, total MAO, CRP, and AST/ALT, causing liver injury. 36 In addition, histamine may regulate metabolic and inflammatory processes in other organs targeted by metabolic syndrome. Two potential mechanisms associated with histamine receptors may attenuate liver injury during the initial and progressive stages of NAFLD in a manner involving the regulation of cholesterol and bile acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Increased levels of its metabolite histamine lead to elevated levels of PARP-1 and IL-1β, as well as MAO-A, total MAO, CRP, and AST/ALT, causing liver injury. 36 In addition, histamine may regulate metabolic and inflammatory processes in other organs targeted by metabolic syndrome. Two potential mechanisms associated with histamine receptors may attenuate liver injury during the initial and progressive stages of NAFLD in a manner involving the regulation of cholesterol and bile acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“… 31 In addition, a preclinical study indicated that tyramine might induce liver damage and adversely affect life conservation. 32 However, the causal relationship between specific species/strains and their derived metabolites in NAFLD pathogenesis has not been fully elucidated, especially in children.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, probiotic fermentation might be an ideal approach to improve the palatability of Chinese medicine plants. However, apart from these advantages, the detrimental effects of probiotic fermentation should also be considered, e.g., the generation of biogenic amines, which cause liver damage, block DNA replication, and disturb biosynthesis [21,22]. Given this point, the safety of the fermentation extract should be explored to ensure the healthy farming of poultry.…”
Section: Introductionmentioning
confidence: 99%